Inklusi Keuangan Syariah sebagai Instrumen Pembangunan Ekonomi Inklusif - Ahmad Fauzan (Economics Note, 2025)
Islamic financial inclusion plays a significant role in promoting inclusive economic development, particularly in Muslim-majority countries. This study aims to analyze the contribution of Islamic financial inclusion in strengthening equitable economic growth through access to Sharia-compliant financial products and services. Using a qualitative descriptive approach, this research examines the development of Islamic financial inclusion in Indonesia by integrating secondary data from Bank Indonesia, OJK, and academic journals. The results show that Islamic financial inclusion positively influences financial accessibility for marginalized communities, enhances micro and small enterprises, and supports poverty alleviation through zakat, waqf, and microfinance institutions. However, challenges remain in public literacy, infrastructure, and regulatory harmonization. The study concludes that comprehensive policy interventions and technological innovation in Islamic finance can accelerate inclusive economic development in Indonesia.